2020
DOI: 10.1038/s41598-020-79102-7
|View full text |Cite
|
Sign up to set email alerts
|

Selenization of S. cerevisiae increases its protective potential in experimental autoimmune encephalomyelitis by triggering an intestinal immunomodulatory loop

Abstract: Multiple sclerosis is an autoimmune disease that affects the myelinated central nervous system (CNS) neurons and triggers physical and cognitive disabilities. Conventional therapy is based on disease-modifying drugs that control disease severity but can also be deleterious. Complementary medicines have been adopted and evidence indicates that yeast supplements can improve symptoms mainly by modulating the immune response. In this investigation, we evaluated the therapeutic potential of Saccharomyces cerevisiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Fraga-Silva et al (166) showed that the administration of Saccharomyces cerevisiae enriched with Se (Selemax) reduced the prevalence of EAE, increased the number of CD103 + dendritic cells and reduced the intestinal inflammatory process compared to the administration of Saccharomyces cerevisiae alone. In addition, Selemax supplementation demonstrated a neuroprotective effect by increasing the expression of protein tau in the CNS.…”
Section: Selenium Microbiota and Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraga-Silva et al (166) showed that the administration of Saccharomyces cerevisiae enriched with Se (Selemax) reduced the prevalence of EAE, increased the number of CD103 + dendritic cells and reduced the intestinal inflammatory process compared to the administration of Saccharomyces cerevisiae alone. In addition, Selemax supplementation demonstrated a neuroprotective effect by increasing the expression of protein tau in the CNS.…”
Section: Selenium Microbiota and Neurological Diseasesmentioning
confidence: 99%
“…In addition, Selemax supplementation demonstrated a neuroprotective effect by increasing the expression of protein tau in the CNS. Tau is the main protein associated with the stability of neuronal microtubules along with the MAPs (MAP1 and MAP2) (166). Long-term dietary supplementation (3 months) with Seenriched yeast (Se-yeast) in triple transgenic mouse model of Alzheimer disease (AD), significantly improved spatial learning, retention of neuronal memory and activity (167).…”
Section: Selenium Microbiota and Neurological Diseasesmentioning
confidence: 99%
“…In the context of MS, supplementation with the probiotic S. cerevisiae has been shown to ameliorate symptoms and the Th1 response in the central nervous system of experimental autoimmune encephalomyelitis (EAE) models. Furthermore, it increases the production of regulatory T cells and enhances microbiota diversity [46]. Other species of the genus Saccharomyces, such as Saccharomyces boulardii, have been suggested to reduce fatigue, pain and inflammation, promote mental health, and improve the quality of life in pwMS [47].…”
Section: Discussionmentioning
confidence: 99%
“…[1] Although the etiology of MS is not well understood, its neuropathological features include demyelination, gliosis, and chronic axonal injury. [2] Moreover, T cell subsets, specially Th1, Th17, and cytotoxic T cells are strongly implicated in the pathogenesis of MS. [3] Lymphocyte infiltration and activation, as well as the microglial and astrocyte activation persist as the defining feature of contemporary MS lesion categorization. [4] Experimental autoimmune encephalomyelitis (EAE) is a widely used animal model for studying human MS, which can help to define the contribution of immune events to the development of MS. [5] Currently, FDA-approved MS therapies act through regulating or inhibiting the peripheral immune response, such as interferon (IFN)-𝛽, dimethyl fumarate, mitoxantrone, glatiramer acetate, and alemtuzumab.…”
Section: Introductionmentioning
confidence: 99%